Analisis Perhitungan PPh final penjualan online sebelum dan sesudah mendapat insentif pajak penghasilan berdasarkan PMK No.9/PMK.03/2021 (Studi Kasus Pada I-support Kediri) - Jesi Melyana; Fauziyah Fauziyah; Siti Isnaniati (JCA (Jurnal Cendekia Akuntansi), 2022)
Estimated tax revenue will increase from year to year. In addition to the number that continues to increase every year, taxes are also the largest source of state revenue. Therefore, it is important for taxpayers to deposit taxes into the state treasury in accordance with applicable regulations. This study aims to find out how to apply the final tax incentives in accordance with applicable regulations given by the government in response to Covid-19. In this study the data used are primary data and secondary data. The analytical method used is descriptive quantitative with data collection techniques in the form of interviews and documentation. The results obtained that the application of tax incentives decreased the comparison of income tax in 2020 before receiving tax incentives was Rp. 19,724,164 and after receiving tax incentives was Rp. 9,859,082. Meanwhile, in 2021, it can be seen from the comparison that before receiving tax incentives it was Rp. 19,840,739 and after receiving it was 10,017,530. the difference before and after incentives in year to year is quite large, namely in 2020 it is 9,865,082 and in 2021 it is 9,823,208. It is hoped that I-Support will be more thorough and updated with changes to existing tax regulations. I-Support is expected to be able to calculate its tax in accordance with the updated regulations. This research is expected to assist researchers in increasing academic knowledge and can provide benefits for other students in conducting research related to online sales income tax incentives. Keywords: tax incentives, final tax, online sales tax